Immune Curbing of Cancer Stem Cells by CTLs Directed to NANOG - Wefers, Christina; Schreibelt, Gerty; Massuger, Leon F. A. G.; de Vries, I. Jolanda M.; Torensma, Ruurd (Frontiers in Immunology, 2018)
Cancer stem cells have been identified as the source of tumor growth and disease recurrence. Eradication of cancer stem cells is thus essential to achieve durable responses, but cancer stem cells are resistant to current anti-tumor therapies. Novel therapeutic approaches that specifically target cancer stem cells will therefore be crucial to improve patient outcome. Immunotherapies, which boost the body’s own immune system to eliminate cancerous cells, could be an alternative approach to target cancer stem cells. Vaccines of dendritic cells loaded with tumor antigens can evoke highly specific anti-tumor T cell responses. Importantly, dendritic cell vaccination also promotes immunological memory formation, paving the way for long-term cancer control. Here, we propose a dendritic cell vaccination that specifically targets cancer stem cells. Dendritic cells loaded with NANOG peptides, a protein specific for cancer stem cells, could evoke a potent anti-tumor immune response against cancer stem cells. We hypothesize that the resulting immunological memory will also control newly formed cancer stem cells, thereby preventing disease recurrence.